Torsion and vibration-torsion levels of the S1 and ground cation electronic states of para-fluorotoluene - Gardner, Adrian M.; Tuttle, William D.; Whalley, Laura; Clayton, Andrew; Carter, Joseph H.; Wright, Timothy G. (American Institute of Physics, 2016)
We investigate the low-energy transitions (0–570 cm-1) of the S1 state of para-fluorotoluene (pFT) using a combination of resonance-enhanced multiphoton ionization (REMPI) and zero-kinetic-energy (ZEKE) spectroscopy and quantum chemical calculations. By using various S1 states as intermediate levels, we obtain zero-kinetic-energy (ZEKE) spectra. The differing activity observed allows detailed assignments to be made of both the cation and S1 low-energy levels. The assignments are in line with the recently-published work on toluene from the Lawrance group [J. Chem. Phys. 143, 044313 (2015)], which considered vibration-torsion coupling in depth for the S1 state of toluene. In addition, we investigate whether two bands that occur in the range 390–420 cm-1 are the result of a Fermi resonance; we present evidence for weak coupling between various vibrations and torsions that contribute to this region. This work has led to the identification of a number of misassignments in the literature, and these are corrected.